Review of Human, Social and intellectual capital in the Covid-19 era - Alejandra, Navarrete Quezada; Cruz, Garcìa Lirios; Alfonso, Aguilar Fuentes (International Journal of Coronaviruses, 2023)
The health and economic crisis caused by the SARS CoV-2 coronavirus and the Covid-19 disease has accelerated the emergence of an informational economy focused on the use of electronic networks. The impact of this scenario on education led to the transition from the traditional classroom to the electronic whiteboard. The objective of the present work was to analyze the relationships between human, social and intellectual capital. A model was established in which the prevalence of human capital formation indicated by data processing in the virtual classroom and self-management of knowledge is appreciated.
Keywords: heads of households; social work; entrepreneurship; specification; mode